La Défense, a Unique Business District - Horn, Christian (project baikal, 2014)
La Défense, the main business cluster of the Paris metropolitan area, had been planned and developed under the impulse of the 1950 onwards. Situated on the historic axis in the west of the city of Paris on the territory of the suburban French State from municipalities of Puteaux and Courbevoie, the basic urban planning principles of this district are strongly influenced by the concepts of the international modern urbanism of this period. The text describes the origin and the development of the site from the project in the 1950s to the construction in the 1960s until the first economic difficulties in the 1970s. It further gives in inside in the recent developments and adjustments of the initial constructions.